EVALUACIÓN DE DOS FUNGICIDAS ORGÁNICOS PARA EL CONTROL DE LA ANTRACNOSIS EN LA LECHOSA (Carica papaya L.) Y SU CALIDAD POSTCOSECHA. (Agroindustria, Sociedad y Ambiente, 2021)
Anthracnose is a disease caused by the fungus Colletotrichum gloeosporioides in lechosa; the objective was to evaluate the effect of two organic fungicides based on oregano (ganore and fungol) on the control of the fungus Colletotrichum gloeosporioides. For this, the isolation of the fungus was carried out; The rate of mycelial growth was evaluated; The pathogenicity of the fungus (koch postulates); The effect of fungicides on the growth of the fungus Colletotrichum gloeosporioides; The effect of fungicides on the fungus Colletotrichum gloeosporioides on the surface of the lechosa and the effect of the fungicides on the postharvest quality of the lechosa. Results were obtained of a 100% inhibitory effect of the two organic fungicides in the different treatments used with concentrations of ganore high dose 15 mL, recommended dose10 mL and low dose 5 mL and fungol; high dose 1,5 mL, 1 mL recommended dose and low dose 0.5 mL; The inhibitory effect of these organic fungicides on the fungus, as in directly applied lechosa fruits; and as in the post- harvest quality evaluation, they maintained the characteristics of appearance, color, pH and total soluble solids (° Brix); likewise, the presence of damages and diseases in the lechosa ones was not observed from the beginning until After 3 days of evaluation. It is concluded that the products based on oregano can be an organic alternative for the control of the fungus Colletotrichum gloeosporioides, naturally and efficiently, without affecting the postharvest quality of the lechosa.
Keywords: Colletotrichum gloeosporioides, lechosa (Carica papaya), oregano.